Learning the language of scripture: origen, wisdom, and the logic of interpretation - James, Mark Randall (Studies in systematic theology, 2021)
Origen and stoic logic -- From lexis to logos -- The pragmatics of scriptural utterances -- The grammar of scriptural language -- The deification of discourse -- Origenism as pragmatism : a sketch of a sapiential hermeneutic.